ANTECEDENTS OF CONSUMERS’ CONTINUOUS INTENTION ON ONLINE PURCHASE: AN EXTENSION OF TAM MODEL (American International Journal of Humanities, Arts and Social Sciences, 2021)
The purpose of this study is to detect and analyze the factors affecting consumers’ attitudes toward online shopping and examine the antecedent’s customer continues intentions to purchase on the online platforms. It also aims to extend and validate the Technology Acceptance Model (TAM) framework in continuous online purchase behavior. The Proposed Model incorporates sevens antecedents (Behavioral factors, Technological Factors, Market Offerings, promotional Factors, attitudes towards online purchase, system effectiveness, and online shopping acceptance). The research employed structured survey questionnaires using 7-scale Likert points. SPSS version 22.0 was used to test the hypothesis and correlation among the factors. The findings indicate that variables like behavioral factors (trust, product attribute, service attribute), technological factors (result demonstration, perceived website reputation), promotions (advertisement, social media, electronic word of mouth), and market offerings (core value) are positively related to attitudes towards online purchase which is positively related to system effectiveness. Both attitudes towards the online purchase and system effectiveness determine the continuous intention to purchase online. This piece of work provides the conceptual framework of continuity of online purchase that can contribute to an academic perspective, and marketers can adopt strategies by understanding the antecedents of online shopping behavior. JEL Classification Codes : M19